Pengaruh Kemandirian, Motivasi, dan Kepribadian terhadap Pengembangan Karir Gen Z di PT Bilah Baja Makmur Abadi - Jocelyne, Jocelyne; Rangkuti, Dhita Adriani; Shella, Shella; Adhitya, Tiara Reizsa (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of independence, motivation, and personality on the career development of Generation Z employees at PT Bilah Baja Makmur Abadi. This study used a quantitative approach and purposive sampling technique, with a sample of 67 Gen Z employees using a questionnaire. The results of multiple linear regression indicate that independence, motivation, and personality, both partially and simultaneously, have a significant influence on career development at PT Bilah Baja Makmur Abadi.